2014
DOI: 10.1080/14729679.2014.950592
|View full text |Cite
|
Sign up to set email alerts
|

The epistemological chain in high-level adventure sports coaches

Abstract: This paper considers the personal epistemology of adventure sports coaches, the existence of the epistemological chain and its impact on professional judgment and decision-making. The epistemological chain's role and operationalization in other fields is considered, offering clues to how it may manifest itself in the adventure sports coach context. Highlevel adventure sports coaches were interviewed and an interpretive phenomenological analysis approach was adopted for the interview transcripts. Based on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…The thematic analysis method adopted in this study was a hybrid of approaches, incorporating an inductive, data-driven method (Boyatzis, 1998); the use of themes (Crabtree & Miller, 1999); and the identification of interactional links between those themes (Axelrod, 1976;Busch, Richards, & Dampney, 2001, 2003Tolman, 1948) and has been utilised in other studies of ASC practice Collins, Collins & Grecic, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thematic analysis method adopted in this study was a hybrid of approaches, incorporating an inductive, data-driven method (Boyatzis, 1998); the use of themes (Crabtree & Miller, 1999); and the identification of interactional links between those themes (Axelrod, 1976;Busch, Richards, & Dampney, 2001, 2003Tolman, 1948) and has been utilised in other studies of ASC practice Collins, Collins & Grecic, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In coaching terms Collins, Collins & Grecic, (2014) identified that the end objective of adventure sports coaches may differ from other sports coaches: a sample of high level ASC had a clear focus to develop a performance that is independent of the coach at a level of adventure appropriate to the individual. These philosophical differences appear to require the ASC to have a very broad range of teaching skills and approaches, some of which are common with other sports coaches and some that are highly contextual to adventure sports (Collins & Collins, 2012, 2013, 2014a, 2014b, 2015a, 2015b.…”
Section: Adventure Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASC is a section of sports coaching which has until recently been underresearched. One of the few existing studies (Collins, Collins, & Grecic, 2015) highlighted the ways in which high-level paddlesport coaches maintain a sophisticated approach to teaching and learning built upon shared common beliefs around (amongst others), the independence of the learner and reflective practice. Unlike most other sports coaches, adventure sports coaches must sustain a high level of skilled performance in order to coach paddlesport in constantly changing water-based environments.…”
mentioning
confidence: 99%
“…Professional judgement and decision making (PJDM; , 2014Collins, Collins, & Grecic, 2015) acts to synergise the complex interactive application of pedagogic and leadership skills associated with coaching practices in adventure sports coaching. Previous papers have highlighted the importance of PJDM in adventure sports coaching specifically as related to risk management (Collins & Collins, 2013), the epistemological underpinning of the PJDM process , and the planning of programmes, linked sessions, and individual sessions .…”
Section: The Focus Of In-action Reflective Practice As a Component Ofmentioning
confidence: 99%